2013
DOI: 10.1155/2013/154812
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Tendon, Ligament, and Enthesis in Response to Genetic Alterations in Key Proteoglycans and Glycoproteins: A Review

Abstract: This review summarizes the genetic alterations and knockdown approaches published in the literature to assess the role of key proteoglycans and glycoproteins in the structural development, function, and repair of tendon, ligament, and enthesis. The information was collected from (i) genetically altered mice, (ii) in vitro knockdown studies, (iii) genetic variants predisposition to injury, and (iv) human genetic diseases. The genes reviewed are for small leucine-rich proteoglycans (lumican, fibromodulin, biglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 161 publications
(209 reference statements)
2
49
0
2
Order By: Relevance
“…TeM expression is observed during tendon fibroblast during maturation (Jelinsky et al, 2010). Moreover, mice lacking TeM display a severe decrease in tenocyte proliferation in the tendons of newborns (Juneja and Veillette, 2013;Docheva et al, 2005). In our in situ hybridization results, strong expression of TeM was found in the middle region of the MM at E12.5 at first and we also found TeM signal in the inserted region of the muscle-bone junction of the MM from E14.5 onward.…”
Section: Discussionsupporting
confidence: 66%
“…TeM expression is observed during tendon fibroblast during maturation (Jelinsky et al, 2010). Moreover, mice lacking TeM display a severe decrease in tenocyte proliferation in the tendons of newborns (Juneja and Veillette, 2013;Docheva et al, 2005). In our in situ hybridization results, strong expression of TeM was found in the middle region of the MM at E12.5 at first and we also found TeM signal in the inserted region of the muscle-bone junction of the MM from E14.5 onward.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast to the organized, distinct development of the four zones of the cartilaginous enthesis, tendonbone healing occurs through the formation of fibrovascular scar tissue and does not reestablish the native tendon-bone insertion site formed during embryological development 1,9,14,[21][22][23] . The work done by Thomopoulos et al 24 stresses the importance of understanding the development and morphogeneses of the tendon-bone enthesis in order to more fully understand the healing process of the insertion site.…”
Section: Tendon Insertion Healingmentioning
confidence: 99%
“…The need for both biological factors and mechanical influences on the development of entheses in combination with the specific composition, function, and mechanical properties of the four zones of fibrocartilaginous entheses makes it extremely difficult to recreate this native insertion. Several studies have reported that the gradations developed in native tendon are not regenerated during tendon to bone healing 14,[21][22][23][28][29][30][31][32] . Furthermore, the resulting fibrovascular scar tissue interface has been shown to be mechanically weaker and more prone to failure than that of the natural tendon-bone enthesis created during prenatal development 9,24,28,33 .…”
Section: Tendon Insertion Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…These fibrils are crosslinked to one another and wrapped in a tendon sheath (Banos et al, 2008;Kannus et al, 1998;Ros et al, 1995). This basic structure is shared among tendons and ligaments, and the fibroblasts that produce the ECM develop from common progenitors with similar gene expression profiles (Juneja and Veillette, 2013;Sugimoto et al, 2013;Tozer and Duprez, 2005;Yang et al, 2013). However, each tendon or ligament differs in its precise ECM composition, size and strength .…”
Section: Introductionmentioning
confidence: 99%